Smith Predictor-based Cross-Coupling Correction for Voltage Source Converters under Mixed Reference Frames - Peng Q.; Yang J.; Guenter S.; Buticchi G.; Tan N.M.L.; Wheeler P. (Institute of Electrical and Electronics Engineers Inc., 2024)
Voltage Source Converters (VSC) have been under the spotlight of scientific research due to the development of the distributed generation system. Synchronous Reference Frame (SRF)-based controllers are readily used for the voltage and current control of these converters due to its simplicity and clear physical significance. However, in machine drive or more electric aircraft (MEA) scenarios, the low switching-to-fundamental (S2F) frequency ratio leads to more significant cross-coupling between d and q axis, which will affect the control accuracy and even jeopardize the system stability. This work proposes a Smith Predictor-based current control under mixed reference frames that is able to eliminate the cross-coupling effect without a sophisticated parameter design process. Experimental results are given to further verify its performance under MEA grid scenario. 2023 The Korean Institute of Power Electronics.